Penulisan Hadis di Masa Ulama Muttaqaddimin (Kodifikasi Kitab Muwaththa’ Imam Malik) - Siddik Firmansyah (Institut Agama Islam Negeri Padangsidimpuan, 2021)
Hadith is the second source of Islamic law. One of the great scholars who compiled the prophetic traditions in book form was Imam Malik. His most phenomenal book is called the al-Muwatta’s book. Terefore, this research aims to explain the biography of Imam Malik, the compilation of hadith before the al-Muwaththa's book, the codification of the al-Muwaththa's book, and the comments of scholars on the al-Muwaththa's book. The method used in this research is the analytical method. The results of the study indicate that Imam Malik is a competent scholar, an expert in the field of fiqh and hadith. Before the time of Imam Malik there was no formal compilation and bookkeeping of the prophet's hadith. Imam Malik was inspired to write the hadith at the request of the Khalifah Abu Ja'far al-Mansyur at the suggestion of Muhammad al-Muqaffa and the bookkeeping of the hadith of the al-Muwattha’s book based on the arrangement of the chapters of fiqh. The scholars agreed on the faith, the greatness of collecting hadith, criticizing the narrators, and extracting laws both in the Qur'an and the Sunnah of Imam Malik.